Effect of HSV‐2 on population‐level trends in HIV incidence in Uganda between 1990 and 2007. Issue 10 (10th September 2013) - Biraro, Samuel; Kamali, Anatoli; White, Richard; Karabarinde, Alex; Nsiimire Ssendagala, Juliet; Grosskurth, Heiner; Weiss, Helen A.
Abstract: Objective: To assess the long‐term effects of population‐level HSV‐2 infection on HIV incidence. Methods: Data from a population‐based cohort in south‐western Uganda were used to estimate HIV incidence from 1990 to 2007. Stored blood samples were tested for HSV‐2, and the impact of HSV‐2 prevalence and incidence on HIV incidence was estimated by calculating population attributable fractions (PAFs). The association between population‐level annual HIV incidence and annual HSV‐2 incidence/prevalence was analysed using linear regression. Results: HIV incidence declined over time among men, from 8.72/1000 person‐years (pyr) in 1990 to 4.85/1000 pyr in 2007 ( P ‐trend <0.001). In contrast, there was no decline in HIV incidence among women (4.86/1000 pyr in 1990 to 6.74/1000 pyr in 2007, P ‐trend = 0.18). PAFs of incident HIV attributable to HSV‐2 were high (60% in males; 70% in females). There was no evidence of an association between long‐term trends in HIV incidence and HSV‐2 prevalence or incidence. Conclusion: Assuming a causal relationship, a substantial proportion of new HIV infections in this population are attributable to HSV‐2. The study did not find an effect of HSV‐2 prevalence/incidence on trends in HIV incidence. HIV incidence did not vary much during the study period. This may partly explain the lack of association.